PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Usmar Usmar; Selfiani Selfiani; Nirwan Mulyatno; Abdullah Abdullah (Jurnal Manajemen dan Bisnis, 2021)
This study aims to examine and analyze the effect of leadership style and motivation on employee performance with a population of PT Boga Berkat Prima Jakarta. The data collection technique was carried out using questionnaires and was intended for 50 employees of PT Boga Berkat Prima Jakarta. The data analysis method in this study uses SPSS Statistics version 24.0 by first using the data testing technique method of validity testing and reliability testing for research questionnaires. Classical assumption test and multiple linear regression analysis, to test and prove the research hypothesis used statistical t test. The results of the analysis show that leadership style has a positive effect on employee performance and motivation also has a positive effect on employee performance